Study on risk factors for postoperative cough in children with hypertrophy of tonsils and adenoids - Jiang, Hong Mei; Meng, Xiao Yu; Zhao, Xing He; Shen, Zi Yu; Dou, Xun Wu (Frontiers in Pediatrics, 2026)
Background/aimsTo investigate the risk factors for postoperative cough in children with tonsil and adenoid hypertrophy following tonsillectomy and adenoidectomy.Materials and methodsA total of 182 children with tonsil and adenoid hypertrophy treated in the Department of Otorhinolaryngology at the Wujiang District Children's Hospital of Suzhou City between January 2024 and December 2024 were selected. They were divided into groups based on the presence or absence of postoperative cough for a comparative study.ResultsStatistically significant differences were found between the two groups regarding patient age, preoperative white blood cell levels, abnormal chest x-ray findings, and the presence of comorbid sinusitis or allergic rhinitis during the perioperative period. Multivariate logistic regression analysis identified younger age and comorbid sinusitis as independent risk factors.ConclusionYounger age and comorbid sinusitis are significant risk factors influencing the occurrence of cough in children after tonsillectomy and adenoidectomy.